2011
DOI: 10.1007/s10646-011-0679-0
|View full text |Cite
|
Sign up to set email alerts
|

Historical record and source apportionment of polycyclic aromatic hydrocarbons in the Lianhuan Lake sediments

Abstract: Polycyclic aromatic hydrocarbons (PAHs) in a sediment core from the north Lianhuan Lake were collected to investigate its historical changes in the last one hundred years and its possible influence on ecological system in the lake. GC-MS was used to determine the concentrations of PAHs, and sediment chronological age was examined by (137)Cs dating approach. The concentrations of 16 different kinds of PAHs in the sediment samples ranged from 297 to 1,327 ng g(-1), and the low molecular weight (LMW) were predomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…Higher molecular weight PAHs (HMW, 4-6 ring) especially 5 and 6-ring PAHs were less prevalent, accounted for a mean of only 1.44 %. These results are consistent with our previous study of PAHs in core sediments in north Lianhuan Lake, where the concentrations of PAHs ranged from 297 to 1,328 ng/g with the LMW components predominated (Sun et al 2011). …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Higher molecular weight PAHs (HMW, 4-6 ring) especially 5 and 6-ring PAHs were less prevalent, accounted for a mean of only 1.44 %. These results are consistent with our previous study of PAHs in core sediments in north Lianhuan Lake, where the concentrations of PAHs ranged from 297 to 1,328 ng/g with the LMW components predominated (Sun et al 2011). …”
Section: Resultssupporting
confidence: 93%
“…As previously reported (Sun et al 2011), the petroleum source of PAHs in the Lianhuan Lake area are thought to result from the lake being adjacent to the Daqing Oilfield and the spilled oil from drilling and transportation processes may result in the accumulated of petroleum in the sediments of the lake. In the current study, the environmental impact of the oilfield was further investigated.…”
Section: Resultsmentioning
confidence: 73%
“…The sediments with higher TOC appeared to exhibit relative the higher PAHs. Previous studies also indicated that PAHs accumulations in the sediments were positively correlated with TOC (Sun et al 2011). Besides, black carbon (BC) also benefited PAHs deposition within the sediments (Bucheli et al 2004;Oen et al 2006;Agarwal and Bucheli 2011).…”
Section: Relationships Among Pahs Toc and Grain Sizementioning
confidence: 92%
“…The concentrations of PAHs in sediments were affected by chemical composition of the sediments such as organic matter and clay contents (Kim et al 1999;Sun et al 2011). In the present study, a significant positive correlation was found between the total organic carbon and the total PAHs concentrations for all the Inner Deep Bay sediment samples with a correlation coefficient value (r) of 0.384 (p \ 0.0001, n = 40) (Fig.…”
Section: Relationship Among Sedimentary Pahs Toc and Psdmentioning
confidence: 99%